Non-right handed primary progressive apraxia of speech - Botha, Hugo (J Neurol Sci, 2018)
In recent years a large and growing body of research has greatly advanced our understanding of primary progressive apraxia of speech. Handedness has emerged as one potential marker of selective vulnerability in degenerative diseases. This study evaluated the clinical and imaging findings in non-right handed compared to right handed participants in a prospective cohort diagnosed with primary progressive apraxia of speech. A total of 30 participants were included. Compared to the expected rate in the population, there was a higher prevalence of non-right handedness among those with primary progressive apraxia of speech (6/30, 20%). Small group numbers meant that these results did not reach statistical significance, although the effect sizes were moderate-to-large. There were no clinical differences between right handed and non-right handed participants. Bilateral hypometabolism was seen in primary progressive apraxia of speech compared to controls, with non-right handed participants showing more right hemispheric involvement. This is the first report of a higher rate of non-right handedness in participants with isolated apraxia of speech, which may point to an increased vulnerability for developing this disorder among non-right handed participants. This challenges prior hypotheses about a relative protective effect of non-right handedness for tau-related neurodegeneration. We discuss potential avenues for future research to investigate the relationship between handedness and motor disorders more generally.